Pemberdayaan Masyarakat Melalui Pembuatan Eco Enzyme dan Sabun Eco Enzyme di Negeri Hatu, Maluku - Novianty C Tuhumury; Alex S W Retraubun; Debby A J Selanno; Mintje Wawo; James Abrahamsz; Arielno Sahalessy; Sumiyanti Sumiyanti (LPMP Imperium, 2025)
The processing of fruit peel waste into an eco-enzyme is a simple and environmentally friendly technology. This community service program aimed to empower the community through the production of eco-enzyme and eco-enzyme soap in Negeri Hatu. This PKM activity was conducted on May 24, 2025, in Negeri Hatu, Leihitu Barat District, Central Maluku Regency, involving 23 women from the local women's service group. The methods used included lectures and training on the production of eco-enzyme and eco-enzyme soap. Participants were provided with a mini-handbook to facilitate understanding of the material. Subsequently, participants were trained in groups to produce eco-enzyme and eco-enzyme soap. Participant enthusiasm was evident from the various questions raised regarding the eco-enzyme and its benefits. After the activity, participants gained knowledge and understanding of the eco-enzyme and its production process, which they had previously lacked. The results of the activity showed that participants successfully practised the production of eco-enzyme and eco-enzyme soap. It is expected that participants will be able to process fruit peel waste into an eco-enzyme in every household as a concrete step toward reducing organic waste and increasing family economic value.